Improving Learning Discipline: The Effect of Self-Management Ability on Students in Mathematics Subjects - Azis, Irawati; Clefoto, Mahlatse (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to describe and interpret the ability to self-manage students' mathematics learning discipline in class VIII Darud Da'wah wal Irsyad Al-Irsyah Makassar junior high school. Methodology: This research uses two variables, namely self-management ability as the independent variable and students' mathematics learning discipline as the dependent variable. The population in this study were all Class VIII students at Darud Da'wah wal Irsyad Al-Irsyah Makassar junior high school. The total sample was 30 class VIII students at Darud Da'wah wal Irsyad Al-Irsyah Makassar junior high school. To obtain data, questionnaire instruments and documentation were used by researchers to mathematics teachers. Main Findings: Based on the results of research and descriptive analysis, the average score for self-management ability is in the good category and the average score for mathematics learning discipline is in the good category. The results of the inferential analysis show that the Rcount value is 0.982, while the Rtable at the 5% significance level is 0.361. Thus, the Rcount value is much greater than the Rtable value, so Ha is accepted, meaning that there is a significant relationship between students' thinking abilities and the mathematics learning discipline of Class VIII students at Darud Da'wah wal Irsyad Al-Irsyah Makassar junior high school. Novelty/Originality of this stud: Through this research, it was found that implementing self-management strategies not only improves students' academic performance but also builds attitudes of responsibility and independence that are essential for long-term success in education.